Efficacy and safety of catheter ablation for atrial fibrillation in patients with cancer. (25th November 2020) - Ganatra, S; Abraham, S; Parikh, R; Kamenetsky, D; Patel, R; Dani, S; Chaudhry, G; Resnic, F; Shah, S; Venesy, D; Patten, R; Neilan, T; et al.
Abstract: Background: Atrial fibrillation (AF) is the most common arrhythmia in patients with cancer. Management of AF in patients with cancer poses unique challenges. Long-term use of antiarrhythmic drug (AAD) therapy lacks evidence of efficacy in this population and poses risk of drug interactions. Catheter ablation is a well-established treatment modality for AAD resistant symptomatic AF and in patients with heart failure. Nevertheless, the effectiveness and safety of catheter ablation in patients with cancer is not well established. Method: We retrospectively analyzed consecutive patients who underwent catheter ablation for AF, with either history of cancer (other than non-melanoma skin cancer) within 5-years prior or exposure to systemic anthracycline and/or thoracic radiation therapy at any time. Results: The study included 162 patients. The mean age was 65.5 (26–84 years) years and 50% were female. Overall 133 (82%) patients had freedom from AF at 12 months following ablation. Of these 74 (54%) required post-ablation AAD, 18 (13.5%) required another ablation within the first 12 months and 9 (6.7%) required both AAD and a second ablation to maintain sinus rhythm. There were 14 adverse events (8.6%); 5 access site and 4 non-access site bleeding, 2 strokes, 2 cardiac tamponade and 1 pulmonary vein stenosis with ≈1% serious complications. Conclusion: The success of catheter ablation for AF and the incidence of procedure related complications in patients with a history of recent cancer or prior exposure to cardiotoxic therapies are similar to that reported in patients without a history of cancer and hence if needed, it should be considered in select patients. Funding Acknowledgement: Type of funding source: Private hospital(s). Main funding source(s): Dr. S Ganatra is supported by Lahey Physician Research Stipend Program.